Questioning the Postmodern: Deguy, Jabès and Pleynet - Joan Brandt (Studies in 20th & 21st Century Literature, 1994)
Theorists of the postmodern tend to see the postmodernist literary text as that which disrupts modernism's inclusive and coherent structures. As opposed to the modernist text, which is characterized as centered, ordered, self-reflexive and autonomous, the postmodernist text is seen as decentered and indeterminate; it blurs the boundaries separating the text from other cultural spheres and questions radically the metaphysics of presence, of the subject, of identity and coherence. This study questions the tendency to see postmodernism in terms of its opposition to modernism. Through an analysis of three contemporary French poets, Michel Deguy, Edmond Jabès and Marcelin Pleynet, it argues that "postmodernist" poetics, while clearly contesting the modernist aesthetic, at the same time upholds many of its precepts. An exploration of these contradictory tendencies reveals that the closural devices of modernism, which are still operative in the "postmodern" text, interact paradoxically with forces that dissolve modernist boundaries and that give the text a more referential or historical dimension. It is thus by underscoring the paradoxes and duplicities that structure the contemporary poetic text that this essay questions the tendency to posit a simple opposition between the textual and the historical, between the self-reflexive and the worldly, between the modern and postmodern, that structures many of the current debates on postmodernism.
Keywords: postmodern theory; postmodernism; modernism; French poetry; poetry; Michel Deguy; Edmond Jabès; Marcelin Pleynet; modernist aesthetic; modern